2014
DOI: 10.1111/echo.12585
|View full text |Cite
|
Sign up to set email alerts
|

Role of Three‐Dimensional Echocardiography in Structural Complications after Acute Myocardial Infarction

Abstract: Three-dimensional echocardiography (3DE) is a unique cardiovascular imaging modality in terms of: ability to provide realistic anatomical views of cardiac structures in the beating heart and possibility to visualize cardiac structures from any desired perspective. Therefore, 3DE is emerging as an accurate imaging modality for a prompt diagnosis and detailed anatomical description of structural complications (SC) of acute myocardial infarction (AMI). We report 3 emblematic cases which show how both the transtho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Three-dimensional TTE or TEE can further elucidate size, location, and morphology of the VSD and may assist in the determination of the appropriateness of a percutaneous approach and in guiding the procedure, such as was used in this case. 5 Because of the low incidence and high mortality of postinfarction VSD, guidelines are based largely on expert consensus and data from small observational studies. Current American College of Cardiology/American Heart Association guidelines recommend emergent surgical repair in all cases of post-MI VSD, though they acknowledge high operative mortality rates up to 87%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional TTE or TEE can further elucidate size, location, and morphology of the VSD and may assist in the determination of the appropriateness of a percutaneous approach and in guiding the procedure, such as was used in this case. 5 Because of the low incidence and high mortality of postinfarction VSD, guidelines are based largely on expert consensus and data from small observational studies. Current American College of Cardiology/American Heart Association guidelines recommend emergent surgical repair in all cases of post-MI VSD, though they acknowledge high operative mortality rates up to 87%.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional TTE or TEE can further elucidate size, location, and morphology of the VSD and may assist in the determination of the appropriateness of a percutaneous approach and in guiding the procedure, such as was used in this case. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Two‐dimensional transthoracic echocardiography (2DTEE) has frequently been used in conjunction with 2DTTE, especially in patients with poor acoustic windows and also to guide its closure in both percutaneous and intraoperative settings . Recently, the use of 2D imaging has been supplemented by 3DTTE in a few case studies reported in the literature . The advent of 3DTEE began with the introduction of 3D reconstruction of 2DTEE images, and initially, this technique was used to comprehensively assess VSR .…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Recently, the use of 2D imaging has been supplemented by 3DTTE in a few case studies reported in the literature. [11][12][13][14] [17][18][19] In one case report, 19 capitalizes on the inherent deficiencies of 2D imaging. 2D imaging is only able to capture a thin slice of a given cardiac structure at any point in time.…”
Section: The Icc For Both Intra-and Inter-observer Variability For Almentioning
confidence: 99%